Clinical Phenotypes and Prognosis of Dilated Cardiomyopathy Caused by Truncating Variants in the TTN Gene. (October 2020) - Akhtar, Mohammed Majid; Lorenzini, Massimiliano; Cicerchia, Marcos; Ochoa, Juan Pablo; Hey, Thomas Morris; Sabater Molina, Maria; Restrepo-Cordoba, Maria Alejandra; Dal Ferro, Matteo; Stolfo, Davide; Johnson, Renee; Larrañaga-Moreira, José M.; Robles-Mezcua, Ainhoa; et al.
Abstract : Background: Truncating variants in the TTN gene (TTNtv) are the commonest cause of heritable dilated cardiomyopathy. This study aimed to study the phenotypes and outcomes of TTNtv carriers. Methods: Five hundred thirty-seven individuals (61% men; 317 probands) with TTNtv were recruited in 14 centers (372 [69%] with baseline left ventricular systolic dysfunction [LVSD]). Baseline and longitudinal clinical data were obtained. The primary end point was a composite of malignant ventricular arrhythmia and end-stage heart failure. The secondary end point was left ventricular reverse remodeling (left ventricular ejection fraction increase by ≥10% or normalization to ≥50%). Results: Median follow-up was 49 (18–105) months. Men developed LVSD more frequently and earlier than women (45±14 versus 49±16 years, respectively; P =0.04). By final evaluation, 31%, 45%, and 56% had atrial fibrillation, frequent ventricular ectopy, and nonsustained ventricular tachycardia, respectively. Seventy-six (14.2%) individuals reached the primary end point (52 [68%] end-stage heart failure events, 24 [32%] malignant ventricular arrhythmia events). Malignant ventricular arrhythmia end points most commonly occurred in patients with severe LVSD. Male sex (hazard ratio, 1.89 [95% CI, 1.04–3.44]; P =0.04) and left ventricular ejection fraction (per 10% decrement from left ventricular ejection fraction, 50%; hazard ratio, 1.63 [95% CI, 1.30–2.04]; P <0.001) were independent predictors of the primary end point. Two hundred seven of 300 (69%) patients with LVSD had evidence of left ventricular reverse remodeling. In a subgroup of 29 of 74 (39%) patients with initial left ventricular reverse remodeling, there was a subsequent left ventricular ejection fraction decrement. TTNtv location was not associated with statistically significant differences in baseline clinical characteristics, left ventricular reverse remodeling, or outcomes on multivariable analysis ( P =0.07). Conclusions: TTNtv is characterized by frequent arrhythmia, but malignant ventricular arrhythmias are most commonly associated with severe LVSD. Male sex and LVSD are independent predictors of outcomes. Mutation location does not impact clinical phenotype or outcomes. Abstract : Supplemental Digital Content is available in the text.